Prioritization of Brand Equity Components Using an Integrated Structural Equation Modelling and Fuzzy AHP - Gelare Mortezaei; Hamidreza Alizadeh Otaghvar; Hossein Vazifehdoost; Parviz Saeedi; Abdolaziz Pegheh (Tehnički Glasnik, 2021)
Brand equity of health tourism is the set of assets (or liabilities) of the brand in relation to the name and symbol of the tourism destination that cause changes in the value of services and experiences that are determined there. Considering the characteristics and cultural, social and economic capacities of Iranian tourism destinations, this study tends to develop a model for brand equity in health tourism, derived from the Acker model, according to Iran's conditions and studies conducted. First, previous studies in this regard were carefully reviewed by meta-synthesis. Then the mixed method including qualitative and quantitative methods was applied. The data were analyzed using grounded theory and MAXQDA18 software and then using structural equation method and fuzzy Analytic Hierarchy Process (Fuzzy AHP). Statistical population included experts including professors in the field of marketing and health tourism specialists for qualitative part, and foreign users of health tourism services of Iran for quantitative part. The results showed that hospital brand equity is directly affected by brand awareness, brand association, perceived quality, brand loyalty, social responsibility, firm value and customer value. As a result, at the national level, investing in this sector and branding and paying attention to brand equity of health tourism can make Iran one of the best health tourism destinations in the world.